Vietnam : 2008 Article IV Consultation; Staff Report; Staff Supplement and Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2009)
Following an extended period of strong economic performance, Vietnam is facing considerable challenges. Growth moderated to 6.2 percent in 2008. Rapid credit growth fueled by massive capital inflows, coupled with a surge in commodity prices, led to high inflation and large trade deficits in the first half of 2008. Executive Directors have commended the Vietnamese authorities for the significant progress they have made in stabilizing the economy, which was overheating in 2008. Directors have also welcomed the recent improvements in inflation and the trade balance.